Obstacle Locating Capabilities of Mobile Robot Using Various Navigational Aids (International Journal of Engineering and Computer Science, 2013)
Automatic path planning is one of the most challenging problems confronted by the autonomous robots. Generating optimal paths for autonomous robots are some of the heavily studied subjects in mobile robotics applications. The environments in which the robots operate can be structured or unstructured. In various applications, environment is detected through vision sensors like cameras. Once the information about the environment is known, then it is always convenient to build a roadmap or graph of the environment. Different algorithms exist in the field of path planning for building the roadmaps. After obtaining the convenient representation of the environment the graph search methods can be used to find the optimal paths through this roadmap. Graph search algorithms are very popular in the field of mobile robotics and finds a lot of applications in this field. This survey aims at analysis of various navigational and path planning algorithms using a mobile robot in structured environment. Along with that it involves the study of lacking behaviors of methods for efficient representation of environment. The environment is detected through camera and then a roadmap of the environment is built using some algorithms. Finally, the algorithm searches through the roadmap and finds an optimal path for robot to move from start position to goal position.